Fahr Disease in Elderly Patients with Bronchopneumonia and History of Ischemic Stroke: A Case Report and Literature Review - Miftahul Hasanah; Aditya Putra Priyahita (Magna Neurologica, 2026)
Background: Fahr's Disease (Fahr's Syndrome) is a rare condition characterized by idiopathic bilateral basal ganglia calcifications, typically occurring in the lateral parts of the globus pallidus, dentate nuclei, and caudate nuclei. Diagnosis is based on clinical features of neuropsychiatric and somatic symptoms in conjunction with radiological findings. We report an unusual case of Fahr's disease in a 70-year-old woman with bronchopneumonia and a history of chronic ischemic stroke identified through a CT-SCAN. Case: The patient was a 70-year-old female, admitted to our emergency department with bronchopneumonia, who presented with declining consciousness and focal seizures for 3 hours before entering the hospital. Her brain’s CT scan revealed calcification in the bilateral lentiform nuclei, bilateral cerebellar dentate nuclei, and left corona radiata, consistent with Fahr's disease. The patient was also diagnosed with bronchopneumonia and chronic ischemic stroke. Discussion: Fahr's Disease is linked to abnormal calcium metabolism, leading to calcifications in the basal ganglia. While chronic ischemic stroke may not directly cause Fahr's Disease, it increases the risk of cerebrovascular events in affected individuals. The correlation between infection and Fahr's Disease is poorly understood, although it may exacerbate neurological symptoms. Conclusion: Basal ganglia calcification in Fahr's disease may be associated with an increased risk of stroke and bronchopneumonia, which can worsen the patient's condition. Further research is needed to understand the relationship between Fahr's disease, ischemic stroke, and infections.